2015
DOI: 10.1038/srep13360
|View full text |Cite
|
Sign up to set email alerts
|

Losing dexterity: patterns of impaired coordination of finger movements in musician’s dystonia

Abstract: Extensive training can bring about highly-skilled action, but may also impair motor dexterity by producing involuntary movements and muscular cramping, as seen in focal dystonia (FD) and tremor. To elucidate the underlying neuroplastic mechanisms of FD, the present study addressed the organization of finger movements during piano performance in pianists suffering from the condition. Principal component (PC) analysis identified three patterns of fundamental joint coordination constituting finger movements in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…) and/or loss of independent movement control between fingers (Furuya et al . ). Here, the novel behavioural findings are the prolonged IKI, IRI and finger‐key contact durations in the MD patients when playing at the fastest tempo (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…) and/or loss of independent movement control between fingers (Furuya et al . ). Here, the novel behavioural findings are the prolonged IKI, IRI and finger‐key contact durations in the MD patients when playing at the fastest tempo (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In a previous kinematic study of piano keystrokes, MD patients with pronounced timing variability displayed reduced independent control of movements between the affected finger and a finger striking a key (Furuya et al . ). Together, the reduced SICI is a candidate biomarker of an FTSD symptom, impairment of individuated finger movements, which possibly underlies the temporally variable keystrokes of pianists with MD.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Specifically, one suggested mechanism, found in several studies of FTSD patients, is the development of impaired surround inhibition, a neural inhibitory mechanism responsible for the selective recruitment and activation of muscles necessary for a particular task with inactivation of the neighboring muscles that are unnecessary [27, 29, 30]. Consistent with the hypothesis of decreased SICI and impaired surround inhibition, multiple studies have shown a loss of dexterity and impaired independent movement of fingers of patients with either writer’s cramp or musician’s dystonia [3133]. …”
Section: Advances In Understandingmentioning
confidence: 99%